Corporate value added tax avoidance. Issue 4 (2nd October 2021) - Zhang, Junsheng; Huo, Zheng; Zeng, Yamin; Tang, Xiaojian; Rui, Oliver M.
ABSTRACT: Previous studies of corporate tax avoidance have focused exclusively on corporate income tax, an important tax for US firms in particular. Value added tax (VAT), which is a significant tax in other major economies in the world, is ignored in the literature. This paper examines corporate VAT avoidance behaviour in the context of China, where both corporate income tax and VAT are critical for firms. We develop a measure of corporate VAT avoidance and, using simultaneous equation regression, we find a complementary relationship between corporate income tax avoidance and VAT avoidance. This indicates that traditional studies that limit their focus to income tax may have underestimated the magnitude of firms' tax avoidance. The negative effect of VAT avoidance on firm value supports extant arguments in the literature that the opaqueness caused by tax avoidance increase the agency cost between shareholders and managers.